Reseña a Gonzalo J., Basso, Determinación judicial de la pena y proporcionalidad con el hecho, Marcial Pons, Madrid, 2019, 429, Páginas., ISBN: 9788491236146 - Cruz Palmera, Roberto (Revista de Derecho de la UNED (RDUNED), 2021)
-